Rare genetic variants in patients with cervical artery dissection. (December 2019) - Traenka, Christopher; Kloss, Manja; Strom, Tim; Lyrer, Philippe; Brandt, Tobias; Bonati, Leo H; Grond-Ginsbach, Caspar; Engelter, Stefan
Introduction: The potential role of genetic alterations in cervical artery dissection (CeAD) pathogenesis is poorly understood. We aimed to identify pathogenic genetic variants associated with cervical artery dissection by using whole exome sequencing. Patients and methods: CeAD-patients with either a family history of cervical artery dissection (f-CeAD) or recurrent cervical artery dissection (r-CeAD) from the CeAD-databases of two experienced stroke centres were analysed by whole exome sequencing. Variants with allele frequency <0.05 and classified as pathogenic by predicting algorithms (SIFT or Polyphen-2) or the ClinVar database were explored. First, we analysed a panel of 30 candidate genes associated with arterial dissection (any site) or aneurysm according to the OMIM (online Mendelian Inheritance of Men) database. Second, we performed a genome-wide search for pathogenic variants causing other vascular phenotypes possibly related to cervical artery dissection. Findings were classified as CeAD-causing (pathogenic variants in genes from the arterial dissection or aneurysm panel) or suggestive (pathogenic variants in genes associated with other vascular phenotypes and variants of unknown significance in genes from the arterial dissection or aneurysm panel). All other variants were classified as benign/uncertain. Results: Among 43 CeAD-patients, 28 patients (17 pedigrees) had f-CeAD and 15 had r-CeAD. No CeAD-causing variants were identified in r-CeAD patients. Among f-CeAD-patients, 5/17 pedigrees carried CeAD-causing variants in COL3A1, COL4A1, COL4A3, COL4A4, COL5A1, COL5A2 and FBN1. Suggestive variants in ABCC6, COL3A1, COL5A2, MEF2A, and RNF213 were detected in three pedigrees with f-CeAD and six patients with r-CeAD. Discussion and conclusion: CeAD-causing variants were rare and exclusively found in f-CeAD-patients, suggesting differences between the genetic architectures of f-CeAD and r-CeAD. The identified variants indicate a high genetic heterogeneity of the study sample.